2019
DOI: 10.1111/cns.13144
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab attenuates reactive astrogliosis via IL‐17RA/(C/EBPβ)/SIRT1 pathway in a rat model of germinal matrix hemorrhage

Abstract: Aims Reactive astrogliosis plays a critical role in neurological deficits after germinal matrix hemorrhage (GMH). It has been reported that interleukin‐17A and IL‐17A receptor IL‐17RA/(C/EBPβ)/SIRT1 signaling pathway enhances reactive astrogliosis after brain injuries. We evaluated the effects of secukinumab on reactive astrogliosis in a rat pup model of GMH. Methods A total of 146 Sprague Dawley P7 rat pups were used. GMH was induced by intraparenchymal injection of collagenase. Secukinumab was administered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…This finding was consistent with previous result based on animal experiments of allograft rejection, T cell-driven retinal disease and germinal matrix hemorrhage. [40][41][42] The mounting evidences on the relationship between SIRT1 and IL-17a in various biological progresses demonstrated that they could be a potential regulation mechanism in other disorders. There was one limitation should be discussed in this experiment.…”
Section: Dovepressmentioning
confidence: 99%
“…This finding was consistent with previous result based on animal experiments of allograft rejection, T cell-driven retinal disease and germinal matrix hemorrhage. [40][41][42] The mounting evidences on the relationship between SIRT1 and IL-17a in various biological progresses demonstrated that they could be a potential regulation mechanism in other disorders. There was one limitation should be discussed in this experiment.…”
Section: Dovepressmentioning
confidence: 99%
“…Other studies have also reported the implication of IL-17A and IL-17AR in GM-IVH pathology due to their role in inflammation and BBB breakdown after stroke. IL-17A and IL-17AR levels are increased, contributing to endogenous reduction of silent information regulator 1 expression and increased cell proliferation markers after collagenase-induced GM-IVH in rats [138]. Similar outcomes have been observed after systemic glycerol administration to neonate rabbits, that show increased reactive microglia and increased levels of pro-inflammatory and chemotactic effector molecules, including IL-1β, IL-6 or TNF-α, IL-8 or MCP [30,63,108].…”
Section: Neuroinflammation and Microglia In Animal Models Of Gm-ivhmentioning
confidence: 56%
“…Short and long-term neuronal death is observed [32], and accumulation and upregulation of iron-handling proteins are also observed around the lesions [133]. However, the effects of the collagenase lesions are also detected in distant regions and cortical thinning [32,131,[136][137][138] as well as cortical tau hyperphosphorylation have been observed [32]. General affection of the brain is supported by the widespread presence of microhemorrhages in the cortex, hippocampus and striatum from P7-lesioned mice the long term (P70) [32] and white matter lesions and basal ganglia loss are also detected after collagenase lesions [131].…”
Section: Collagenase-induced Gm-ivh In Rodentsmentioning
confidence: 99%
“…GMH is a one of the most devastating stroke subtypes for newborns, where the major neurological complications after hemorrhage are neuroinflammation, cerebral palsy, PHH, and motor and cognitive deficits [ 36 ]. Currently, GMH research has primarily focused on neuroinflammation [ 29 , 37 ], reactive astrogliosis [ 31 , 35 ], blood-brain barrier (BBB) destruction [ 38 , 39 ], and hematoma resolution [ 12 , 40 ] which has been closely associated with hematoma. In this study, our focus is on the blood clot which is primary causative factor in GMH-induced secondary brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…To be better observed and measured, histological slices were stained by Nissl. Ventricular volume and cortical thickness were evaluated as previously described in [ 31 ]. The brains were embedded with Optimal Cutting Temperature (OCT, Fisher Scientific, Waltham, MA) and sectioned into 20 μ m thick slices (Leica Microsystems, LM3050S).…”
Section: Methodsmentioning
confidence: 99%